ANALISIS KOMPARATIF MANAJEMEN STRATEGIS GREEN OFFICE ANTARA BADAN PENGEMBANGAN DAN PEMBERDAYAAN SDM KESEHATAN (BPPSDMK) DAN SEKRETARIAT JENDERAL (SEKJEN) DI LINGKUNGAN KEMENKES RI - Ida Umarul Mufidah (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2017)
This research aims to know the Comparative strategic management and implementation of green office among the development and empowerment of human resources for health (BPPSDMK) and the Secretariat-General (GENERAL SECRETARY) of the Ministry of health of the Republic of Indonesia in the Green Office Guideline Standards and Healthy. The research method used was multiple case study approach to comparative analysis. Research conducted in November 2016 s/d in March 2017.The research results of the implementation of strategic management BPPSDMK better than the SECRETARY-GENERAL in meeting the guidelines of the Office of the Green and healthy, it is also corroborated by scoring a total of strategic management BPPSDMK 15 (75%) while the total performance of the SECRETARY-GENERAL of 9 (45%) total performance.